Implementasi Pelayanan Publik Keliling Bupati Ngantor Di Desa (Bunga Desaku) di Desa Panti Kecamatan Panti Kabupaten Jember - Adi Purnomo Adi Purnomo; Putri Robiatul Adawiyah (JURNAL PARADIGMA MADANI : Ilmu Sosial, Politik dan Agama, 2026)
This study is motivated by limited access to public services in rural areas, particularly in Panti District, Jember Regency. The Bupati Ngantor di Desa (Bunga Desaku) program is an innovation in public service delivery using a proactive outreach approach. This study aims to analyze the implementation of the program using George C. Edwards III's policy implementation theory. This research uses a qualitative descriptive method with data collection techniques including interviews, observation, and documentation. The results show that the program implementation runs quite well based on communication, resources, disposition, and bureaucratic structure. The program improves accessibility, efficiency, and community satisfaction. However, several obstacles remain, such as limited service time, uneven socialization, and limited human resources.